Reading comprehension in the foreign language from a discourse perspective - Vanegas Torres, Norma Sofía (Colombian Applied Linguistics Journal, 2010)
Reading comprehension is a well-known phenomenon that has been researched widely; however, further investigations continue opening new routes. Understanding comprehension as the ways in which the reading articulate their life and actions to the texts they encounter is one of the routes to follow. This article reviews some studies about reading focused on cognitive perspectives as well as others that are focused on a broad view of the language from Bajtin/Voloshinov’s ideas and its influence on reading as a historical and ideological practice where there is an encounter of subjectivities with a responsive capability. Besides, the discussion is enriched by some of Foucault’s (2005) principles which are valuable to change the ways of undurstanding comprehension. Acknowledging, first that readers in a foreign language might be socio-cultural foreigners, second that the formal approaches on language are not enough for readers in a foreign language and third, that the turn from the cognitive perspective to the language awareness is convenient for the reading practices, this article presents some reflections on each one of these issues and finally, deals with the discursive view of the language and its consequences for reading in L1 and L2.